PEMBERIAN KOLKHISIN DENGAN LAMA PERENDAMAN BERBEDA PADA INDUKSI POLIPLOIDI TANAMAN PACAR AIR (IMPATIENS BALSAMINA L.) - Wiendra, Ni Made Sastriyani; Pharmawati, Made; Astiti, Ni Putu Adriani (Jurnal Biologi Udayana; Vol 15 No 1 (2011): Jurnal Biologi, 2011)
The purpose of this research was to induce polyploidy on Impatiens balsamina L. Seedlings of I. balsamina was immersed in 0,01% colchicines solution for 4, 6, 8, and 24 hours. Chromosome of I. balsamina was visualized using squash method stained with aceto-orcein. Morphological observations were conducted on plant height, stem circumference, leaf length and width, number of branches flowering time and size of flower. The result revealed that 0,01% solution of colchicine was able to induce polyploidy on I. balsamina. Obsevation on morphological characteristic showed that colchicine treatment increased plant height, stem circumference, leaf length and number of branches. Colchicine treatment induced earlier flowering time, but flower size was unaffected. Twelve chromosomes (2n = 2x = 12) were observed in the diploid seedlings while 25 chromosomes were observed in the tetraploid (2n = 4x = 24 seedlings.
Keywords: Aceto-orcein, chromosome, colchicines, Impatiens balsamina L.